2013
DOI: 10.3390/chemosensors1030068
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical Sensing of Flunitrazepam Based on Screen Printed Graphene Electrodes

Abstract: We present a new electrochemical sensor for Flunitrazepam using disposable and economic Screen Printed Graphene Electrodes. It was found that the electrochemical response of this sensor was improved compared to Screen Printed Graphite Electrodes and displayed an excellent analytical performance for the detection of Flunitrazepam. Those characteristics could be attributed to the high Flunitrazepam loading capacity on the electrode surface and the outstanding electric conductivity of graphene. The methodology is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…An identical behaviour was exhibited by all investigated compounds. In addition, similar observations were reported in the literature on the oxidation of benzodiazepine derivative flunitrazepam [15].…”
Section: Ph Dependency By CVsupporting
confidence: 87%
“…An identical behaviour was exhibited by all investigated compounds. In addition, similar observations were reported in the literature on the oxidation of benzodiazepine derivative flunitrazepam [15].…”
Section: Ph Dependency By CVsupporting
confidence: 87%
“…The voltammogram related to flunitrazepam-contaminated samples shows two important differences compared to the voltammogram of the control samples. First, a broad less intense peak between -0.2 and +0.2 V, which could be attributed to a redox process of 7-aminoflunitrazepam, 41 a pharmacologically active metabolite of flunitrazepam. The scan initiates at +1.0 V, promoting the oxidation of the amine group to hydroxylamine, which is back reduced to the amine, as described by equation 15, and giving rise to peak 1 (Figure 1b).…”
Section: Electrochemical Analysismentioning
confidence: 99%
“…Various studies have been reported which are claiming to produce a nail polish that will reveal the presence of "date rape drugs" such as Rohypnol and GHB by changing color in their presence. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (Students Develop Nail Polish That Can Detect Date Rape Drugs) ( Table 2). Table 1 International legal scenario…”
Section: Various Analytical Procedures Reported For the Determinationmentioning
confidence: 99%